Pengaruh Free Float Terhadap Likuiditas Saham Pada Perusahaan LQ45 Yang Terdaftar Bursa Efek Indonesia Tahun 2019-2023 - Vincensa Prisila Oktaviani; Anthon S.Y. Krihi; Maria Prudensiana L. Muga (Jurnal Riset Ekonomi dan Akuntansi, 2025)
This study aims to determine the effect of the independent variables free float (FF) or shares circulating in the public and the control variables Return on Asset (ROA), Return on Equity (ROE) and Earning per Share (EPS) on the dependent variable, namely Stock Liquidity (TVA) which is measured by the level of stock trading volume in LQ45 Companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This study is a study using a quantitative approach and the type of data used is secondary data sourced from the annual financial reports of LQ45 companies on the Indonesia Stock Exchange with an observation period of five years (2019-2023). The population in this study were 45 companies included in the LQ45 company and there were only 8 companies that were the research samples. This study uses panel data, namely a combination of time series and cross-section data using data analysis technique multiple linear analysis. Based on the results of the study and data analysis, it shows that partially the free float variable has a significant effect on stock liquidity, while the control variable return on assets (ROA) does not have a significant effect, return on equity (ROE) has a significant effect and earnings per share (EPS) has a significant effect on stock liquidity. Simultaneously, the free float variable, return on assets (ROA), return on equity (ROE) and earnings per share (EPS) together affect stock liquidity. The result of the determinant coefficient is 0.279, meaning that 27.9% of the stock liquidity variable can be explained by the free float variable, return on assets (ROA), return on equity (ROE) and earnings per share (EPS). The remaining 72.1% is explained by factors outside this research model.